(64)Cu and fluorescein labeled anti-miRNA peptide nucleic acids for the detection of miRNA expression in living cells - Croci, Stefania (Sci Rep, 2019)
MiRNAs are single stranded RNAs of 18–22 nucleotides. They are promising diagnostic and prognostic markers for several pathologies including tumors, neurodegenerative, cardiovascular and autoimmune diseases. In the present work the development and characterization of anti-miRNA radiolabeled probes based on peptide nucleic acids (PNAs) for potential non-invasive molecular imaging in vivo of giant cell arteritis are described. MiR-146a and miR-146b-5p were selected as targets because they have been found up-regulated in this disease. Anti-miR and scramble PNAs were synthesized and linked to carboxyfluorescein or DOTA. DOTA-anti-miR PNAs were then labelled with copper-64 ((64)Cu) to function as non-invasive molecular imaging tools. The affinity of the probes for the targets was assessed in vitro by circular dichroism and melting temperature. Differential uptake of fluorescein and (64)Cu labeled anti-miRNA probes was tested on BCPAP and A549 cell lines, expressing different levels of miR-146a and -146b-5p. The experiments showed that the anti-miR-146a PNAs were more effective than the anti-miR-146b-5p PNAs. Anti-miR-146a PNAs could bind both miR-146a and miR-146b-5p. The uptake of fluorescein and (64)Cu labeled anti-miR-146a PNAs was higher than that of the negative control scramble PNAs in miRNA expressing cells in vitro. (64)Cu-anti-miR-146a PNAs might be further investigated for non-invasive PET imaging of miR-146 overexpressing diseases.